Acquisition of maltose chemotaxis in Salmonella typhimurium by the introduction of the Escherichia coli chemosensory transducer gene. - Mizuno, T (1986)
Escherichia coli and Salmonella typhimurium are closely related species. However, E. coli cells show maltose chemotaxis but S. typhimurium cells do not. When an E. coli chemotransducer gene (tarE), the product of which is required for both aspartate and maltose chemotaxis, was introduced by using a plasmid vector into S. typhimurium cells with a defect in the corresponding gene (tarS), the transformant cells acquired the ability for both aspartate and maltose chemotaxis. In contrast, when the tars gene was introduced into tarE-deficient E. coli cells, the transformant cells acquired aspartate chemotaxis but not maltose chemotaxis. These results indicate that the absense of maltose chemotaxis in S. typhimurium is a consequence of the properties of the tars gene product.